1997
DOI: 10.1200/jco.1997.15.3.987
|View full text |Cite
|
Sign up to set email alerts
|

Phase II study of liposomal doxorubicin in refractory ovarian cancer: antitumor activity and toxicity modification by liposomal encapsulation.

Abstract: Liposomal doxorubicin has substantial activity against ovarian cancer refractory to platinum and paclitaxel. The responses achieved with liposomal doxorubicin were durable and maintained with minimal toxicity. This liposomal formulation should be evaluated further in combination with other drugs in less refractory patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
269
0
5

Year Published

1999
1999
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 590 publications
(281 citation statements)
references
References 16 publications
7
269
0
5
Order By: Relevance
“…Mucositis was also rare and mild. No infusionrelated reactions, which are sometimes seen in cases of liposomal drug administration (Uziely et al, 1995;Muggia et al, 1996;Stewart et al, 1998;Gordon et al, 2001), occurred in this trial. Ultimately, this phase I study showed that the recommended dosage of NK911 (50 mg m À2 ) using a 3-week schedule was similar to the recommended dosage of free DXR (40 -60 mg m À2 ).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Mucositis was also rare and mild. No infusionrelated reactions, which are sometimes seen in cases of liposomal drug administration (Uziely et al, 1995;Muggia et al, 1996;Stewart et al, 1998;Gordon et al, 2001), occurred in this trial. Ultimately, this phase I study showed that the recommended dosage of NK911 (50 mg m À2 ) using a 3-week schedule was similar to the recommended dosage of free DXR (40 -60 mg m À2 ).…”
Section: Discussionmentioning
confidence: 66%
“…Doxil is comprised of doxorubicin (DXR) encapsulated in STEALTHt liposomes, which are composed of a phospholipid bilayer with surface-bound methoxypolyethyleneglycol. Doxil recently received the US Food and Drug Administration's (FDA) approval for use in the treatment of Kaposi sarcoma or ovarian cancer after the clinical benefits of this drug were clearly shown in recent clinical trials (Muggia et al, 1996;Stewart et al, 1998;Gordon et al, 2001).…”
mentioning
confidence: 99%
“…Liposomal drug delivery systems with doxorubicin have been extensively investigated in relapsed ovarian cancer (Muggia et al, 1997), breast cancer (Ranson et al, 1997) and others (Law et al, 1994;Schwartz and Caspar, 1995;Ellerhorst et al, 1999;Harrington et al, 2001;Judson et al, 2001). A number of trials have been performed with polymer -doxorubicin conjugate where there is covalent linkage of polymer to doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…Recent successes in this area of clinical research include the efficacy of liposomal doxorubicin in AIDS-related Kaposi's sarcoma and patients with refractory ovarian cancer (Muggia et al, 1997;Northfelt et al, 1997). Although the precise mechanisms by which liposomes selectively enter tumours and release drug are not completely understood, their successful application with doxorubicin has led to a resurgence of interest in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Using this approach it is feasible that high plasma levels of free cisplatin, which are associated with the side effects of the drug, may be reduced whilst at the same time allowing more specific targeting of cisplatin to the tumour. This type of liposome delivery system has previously been used successfully for the delivery of doxorubicin in both animal and patient studies (Papahadjopoulous et al, 1991;Vaage et al, 1992;Uziely et al, 1995;Muggia et al, 1997).…”
mentioning
confidence: 99%